ROLE OF THE AGRICULTURAL INITIATIVE AND SUPPORTING AGENCIES IN THE DEVELOPMENT OF PALM GROVES IN DIWANIYA AND MUTHANNA PROVINCES - & Naji, Hamza (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this research is to identify the role of the agricultural initiative and the supporting devices in the development of palm orchards in Diwaniyah and Muthanna provinces. The aims of the research a questionnaire was prepared consisting (62) items distributed over (7) roles. The provinces of Diwaniyah and Muthanna were chosen for conducting the research. The owners of palm orchards benefiting from the agricultural initiative in the development of palm orchards in the provinces of Diwaniyah and Muthanna were (623) borrowers: including (294) borrowers for the establishment of modern palm groves and (329) borrowers  for the development and service of existing palm orchards. A random sample 20% was selected from the research society, with a sample of (125) namely: (59) for the establishment of a modern palm grove and (66) for the development and servicing of existing palm orchards. The results of the research found that the numbers of palm orchards established through the agricultural initiative reached (294) and the numbers of orchards developed and served were (329). The numbers of palm trees planted through the establishment of modern palm groves on agricultural initiative loans amounted to (113978) palm trees. Also, the results found the extension agencies carried out (288) extension activities related to the development of palm orchards in the research area during the agricultural initiative period. The average percentage of the extension role paragraphs was 73%. But, the average percentage of the prevention role paragraphs was 69% in the field of modern palm groves. However, 70% in the development and service of existing palm orchards and the average percentage of the follow-up role paragraphs  reached 75%. The research recommends the continuation of the agricultural initiative through the launch of a new initiative for the development of palm orchards such as the comprehensive agricultural initiative to promote the palm sector.